Fight or Flight? How Do Firms Adapt Their Product Mix in Response to Demand and Competition - Luca Macedoni; Rui Zhang; Frederic Warzynski (CESifo GmbH, 2024)
We propose a new model of multi-product firms in international trade, where firms choose their product mix based on the products' attractiveness and endogenous competition. The model is motivated by two novel stylized facts using Danish manufacturing data, which demonstrate the importance of product-specific characteristics in understanding firms' product mix choices. The model predicts that as a larger number of firms want to supply products with high attractiveness, these products also feature the toughest competition. Depending on the strength of competition, two sorting patterns are possible: one in which only the most productive firms produce the most attractive products and another in which all firms produce the most attractive products. Our model can generate both sorting patterns depending on the value of a key preference parameter. By quantifying our model, we find that product-specific differences in attractiveness and competition explain a quarter of the variation in sales. Furthermore, we find that the most attractive products tend to be produced by all firms, while the least attractive products are made only by the most productive firms.
Keywords: F12; F14; L11; L25; 330; multi-product firms; competition; product attractiveness; sorting